Automatic application of periodic boundary conditions in meso analysis of composite solid propellant. Issue 1 (February 2021) - Qiao, Dong; Qiang, Hongfu; Feng, Shuaixing
Abstract: In the meso numerical simulation of composite solid propellant, the periodic boundary conditions are difficult to be applied due to the complexity of the model and the number of element nodes, which makes it not widely used in the meso analysis. Therefore, based on the periodic boundary condition theory, this paper adopts ABAQUS_Python secondary development, periodic boundary conditions were applied to the meso numerical model of composite solid propellant by Python script under three working conditions of two-dimensional principal axis direction and plane shear direction. The results show that the deformation and stress distribution of the numerical model of composite solid propellant conform to the characteristics of periodic boundary conditions.